LOW TEMPERATURE ABIOGENIC SYNTHESIS OF DOLOMITE - Babǎn J.; Ševc J. (My University, 2001)
Endowed with the theoretical knowledge of carbonate evaporation and the precipitation of CaMg carbonates from aqueous solutions the authors systematically researched the low temperature: formation of dolomite-like carbonates. The results obtained at 40 degreesC indicate that the formation of rhombohedral CaMg carbonates depends on the solid matter/water ratio (solidus index Is). The higher the ratio, the mure MgCO3 enters into the carbonate structure. The results also confirm a gradual transition of these relationships from calcite, through Mg-calcite, Ca-dolomite and Q-dolomite (Quasi-dolomite) to Mg-dolomite (Ca44Mg56). The structure of these synthesised carbonates: is disordered, much like their natural counterparts in lagoons, sabkhas, soil:; etc. When studying Ca-dolomite in the laboratory it was found to restructure into stable dolomite at 100 degreesC and into calcite at 180 degreesC. Synthetized dolomite (Ca50Mg50) does not show superstructural X-ray reflections and hence it was denominated as a Quasi-dolomite (Q-D).